Dissociation of BDNF Val66Met polymorphism on neurocognitive functioning in military veterans with and without a history of remote mild traumatic brain injury. Issue 6 (22nd July 2020) - Merritt, Victoria C.; Clark, Alexandra L.; Evangelista, Nicole D.; Sorg, Scott F.; Schiehser, Dawn M.; Delano-Wood, Lisa
Abstract: Objective: Since neurocognitive functioning following mild traumatic brain injury (mTBI) may be influenced by genetic factors that mediate synaptic survival and repair, we examined the influence of a common brain-derived neurotrophic factor (BDNF) polymorphism (Val66Met) on cognition using a well-defined sample of military Veterans with and without a history of mTBI. Method: Participants included 138 Veterans (mTBI = 75; military controls [MCs] = 63) who underwent neuropsychological testing, including completion of self-report measures assessing psychiatric distress, and BDNF genotyping. The mTBI group was tested roughly 66.7 months following their most recent mTBI. Veterans were divided into two groups—Met+ (Met/Met and Met/Val; n = 49) and Met− (Val/Val; n = 89) and compared on domain-specific cognitive composite scores representing memory, executive functioning, and visuospatial speed. Results: ANCOVAs adjusting for psychiatric distress, sex, years of education, and ethnicity/race revealed a significant group (mTBI vs. MC) by BDNF genotype (Met + vs. Met−) interaction for the memory ( p = .024; ηp 2 = .039) and executive functioning ( p = .010; ηp 2 = .050) composites, such that Met+ mTBI Veterans demonstrated better performance than Met− mTBI Veterans on the cognitive measures, whereas Met+ MCs demonstrated worse performance relative to Met− MCs on the cognitive measures. No significant interaction was observed for the visuospatial speed composite ( p = .938; ηp 2 < .001). Conclusions: These findings offer preliminary evidence to suggest that the Met allele may be protective in the context of remote mTBI. Findings need to be replicated using larger samples, and future studies are necessary to elucidate the precise mechanisms and neural underpinnings of this interaction.